Aerial view showing $2,750,000 Science Building (foreground), built in 1957 (1956)
Caption reads: 'Back of it is the $1,500,000 Engineering Building completed in Summer of 1957. Also shown are several of the temporary metal buildings still available for classroom and other use.' Back of photo reads: 'Aerial Views: Main Campus: General Views - looking west from Science to Business Administration and Education (Ca. 1956-1957).'